Pricing collateralised options in the presence of counterparty credit risk: An extension of the Heston–Nandi model - Venter, Pierre J.; Maré, Eben (South African Statistical Journal, 2022)
In this paper, a closed-formexpression for a collateralised European option in the presence of counterparty credit risk and stochastic volatility is derived. The model is applied to Standard and Poor’s 500 index options. The model prices obtained are consistent with expectations.